Chromatographic characterization of juice in fruits of different Japanese quince (Chaenomeles japonica L.) genotypes cultivated in Sweden - Hellín, María Pilar; Jordán, María José; Rumpunen, Kimmo; Ros, José María (Emirates Journal of Food and Agriculture, 2020)
The juice in fruits of 19 genotypes of Japanese quince (Chaenomeles japonica), representing plant breeding material, was characterised using high performance liquid chromatography. The juice was extracted by halving and squeezing the fruit. Samples of Japanese quince juice were always analysed fresh. The main compounds found were sugars: glucose (131-1056 mg 100 ml-1), fructose (351-2515 mg 100 ml-1) and sorbitol (10-367 mg 100 ml-1); organic acids: malic acid (2.27-4.84 g 100 ml-1) and quinic acid (0.50-2.50 g 100 ml-1); amino acids: aspartic acid (0.8-10.7 mg 100 ml-1), asparagine (0.2-36.3 mg 100 ml-1) and glutamic acid (6.2-17.7 mg 100 ml-1); the cation potassium (145-214 mg 100 ml-1) and the anion fluoride (21-122 mg 100 ml-1). These results on composition suggest that Japanese quince may be an interesting raw material source of valuable substances and its juice an ingredient for the food industry. A principal components analysis separated the Japanese quince genotypes, thus indicating a clear difference in the chemical composition of the juice.